Outcome of Gamma Knife radiosurgery for trigeminal neuralgia associated with neurovascular compression. (January 2018) - Chang, Cheng-Siu; Huang, Cheng-Wei; Chou, His-Hsien; Lin, Long-Yau; Huang, Chuan-Fu
Highlights: Retrospective review of 130 patients with trigeminal neuralgia (TN) treated by Gamma Knife radiosurgery (GKRS). To evaluate whether neurovascular compression (NVC) has prognostic value for pain relief in idiopathic TN treated by GKRS. The presence and type of NVC did not affect pain outcome for TN patients. The lack of poorer response associated with large vessel NVC may be explained by treatment of multiple 4 mm shots. Abstract: We reviewed 130 patients from 1999 to 2012 to evaluate whether neurovascular compression (NVC) has prognostic value for pain relief in idiopathic trigeminal neuralgia (TN) treated by Gamma Knife radiosurgery (GKRS). Patients were assigned to one of the following groups based on NVC identified by MRI: no NVC, small vessel NVC, and large vessel (defined as part of the vertebrobasilar arterial system) NVC. Follow-up ranged from 4 to 14 years. Primary outcome was pain graded by the Barrow Neurological Institute (BNI) pain scale. Successful pain control was defined as a score within Grade I-IIIb. Among the 130 patients, 53 had no neurovascular compression (group 1), 60 had a small vessel NVC (group 2), and 17 had a large vessel NVC (group 3). Successful pain control was 85% in group 1, 75% in group 2, and 88% in group 3 (X 2 = 2.480, p = .289). Secondary outcome was new onset facial numbness which was 21% in group 1, 28% in group 2, and 35% in group 3 (X 2 = 1.683, p = .431). NVC did not affect pain outcome for TN patients treated by GKRS. The lack of poorer response with large vessel NVC that has been reported in literature may be explained by treatment of multiple 4 mm shots (as opposed to a single shot in 11/17 patients) to cover a larger compression area of the nerve root by a tortuous vessel.